2019
DOI: 10.1186/s13075-019-1826-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric validation of the EuroQoL 5-dimension (EQ-5D) questionnaire in patients with spondyloarthritis

Abstract: BackgroundSpondyloarthritis (SpA) has a significant impact on patients’ quality of life due to functional impairments. Generic health instruments like the EuroQoL 5-dimension (EQ-5D) is important for the cost-utility analysis of health care interventions and calculation of quality-adjusted life years. However, the applicability of the EQ-5D health measure in Chinese patients with SpA is currently unknown. Hence, the aim of the study is to test the psychometric properties and to validate the use of the EQ-5D he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 40 publications
1
28
2
Order By: Relevance
“…The ICHOM proposed instruments to measure patient-reported health status [EORTC-QLQ-C30 ( 24 ) and the LC specific version QLQ-LC13 ( 25 )] were not deemed appropriate in the Spanish setting, as they are burdensome to complete and their use is limited in routine clinical practice. Instead, consensus was reached to use the generic questionnaire EuroQol EQ-5D ( 26 , 27 ), that is currently widely used in the Spanish setting, and the LC specific questionnaire Lung Cancer Symptom Scale (LCSS) ( 28 ), for which a Spanish validated version is already available. The combined use of both questionnaires allows to gather information about patient perspective on their physical and emotional functioning, fatigue, vitality, pain, cough, breathing difficulty, hemoptysis, and loss of appetite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ICHOM proposed instruments to measure patient-reported health status [EORTC-QLQ-C30 ( 24 ) and the LC specific version QLQ-LC13 ( 25 )] were not deemed appropriate in the Spanish setting, as they are burdensome to complete and their use is limited in routine clinical practice. Instead, consensus was reached to use the generic questionnaire EuroQol EQ-5D ( 26 , 27 ), that is currently widely used in the Spanish setting, and the LC specific questionnaire Lung Cancer Symptom Scale (LCSS) ( 28 ), for which a Spanish validated version is already available. The combined use of both questionnaires allows to gather information about patient perspective on their physical and emotional functioning, fatigue, vitality, pain, cough, breathing difficulty, hemoptysis, and loss of appetite.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, and in line with ICHOM recommendations, it was agreed to collect both variables at baseline and during patients' follow up. As previously indicated, ECOG scale ( 23 ) was selected to assess patients' performance status, while the EQ-5D ( 26 , 27 ) and LCSS questionnaire ( 28 ) were chosen for the assessment of patients' HRQoL.…”
Section: Resultsmentioning
confidence: 99%
“…In 1990, the EuroQol group developed a health-related quality of life questionnaire (EQ-5D) consisting of five dimensions (mobility, self-care, main activities, social relationships, pain and mood) and an EQ visual analogue scale (score 0–100) to be used for describing a non-disease specific health status (14). Studies on patients with SpA have shown a negative correlation between EuroQol and SpA disease activity scores, such as BASDAI and ASDAS (1516).…”
Section: Methodsmentioning
confidence: 99%
“…Test-retest reliability Responsiveness China + H [21, 27, 28, 41-43, 45, 57, 72, 75, 76, 82, 83, 85, 87, 89, 90] ± H [27,41,75] Hong Kong + H [17,18,20,70,79] ± L b [20,70,79] SF-6D and EQ-VAS, and to explore ways to improve their performance in Asian populations. This study has three limitations.…”
Section: Construct Validitymentioning
confidence: 99%